2020
DOI: 10.1017/s1478951520000486
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural validation of the Cancer Stigma Scale in the general Japanese population

Abstract: Abstract Background The stigma associated with cancer has negative impacts on cancer patients as well as the general public, who have a potential risk of cancer. To the best of our knowledge, a validated measure to assess cancer stigma among the general Japanese population does not exist. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…First, the scale used to measure the COVID-19 stigma was not validated in advance. Developing and validating a new scale for the COVID-19 stigma takes time, and thus we attempted to measure COVID-19 stigma using a validated stigma scale in Japanese for cancer (J-CASS) by changing the disease name ( 22 , 28 ). Nevertheless, our findings demonstrated that the validity measures of the score were satisfactory, suggesting that the scale could be perceived as indicating COVID-19 stigma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the scale used to measure the COVID-19 stigma was not validated in advance. Developing and validating a new scale for the COVID-19 stigma takes time, and thus we attempted to measure COVID-19 stigma using a validated stigma scale in Japanese for cancer (J-CASS) by changing the disease name ( 22 , 28 ). Nevertheless, our findings demonstrated that the validity measures of the score were satisfactory, suggesting that the scale could be perceived as indicating COVID-19 stigma.…”
Section: Discussionmentioning
confidence: 99%
“…We measured stigma related to COVID-19 based on the Japanese version of the Cancer Stigma Scale (J-CASS) ( 28 ), which is a translated version of the original CASS consisting of 25 items ( 22 ). J-CASS was provided by researchers at the Center for Cancer Control and Information Services, National Cancer Center, Japan.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations